Perceived Ability and School Choices: Experimental Evidence and Scale-up Effects - Matteo Bobba; Veronica Frisancho; Marco Pariguana (Institute of Labor Economics (IZA), 2023)
This paper studies an information intervention designed and implemented in the context of a school assignment mechanism in Mexico City. We find that providing students from socio-economically disadvantaged backgrounds with feedback about their academic performance contributes to placing applicants in schools that better fit their skills, allowing them to graduate on time from high school at a higher rate. We also quantify the effect of a counterfactual and yet feasible implementation of the information intervention at a much larger scale. Simulation results demonstrate substantial heterogeneity in the demandside responses, which trigger sorting and displacement patterns within the assignment mechanism. The equilibrium effects of the intervention may possibly hinder the subsequent academic trajectories of high-achieving and socio-economically disadvantaged students.
Keywords: D83; I21; I24; J24; 330; subjective expectations; information provision; school choice; upper-secondary education; scaling up experiments; spillover and equilibrium effects